Correlation of mesolevel characteristics of the healthcare system and socioeconomic inequality in healthcare use: a scoping review protocol - Matthias Richter; Nico Dragano; Irene Moor; Benjamin Wachtler; Leonie Sundmacher; Katharina Diehl; Jacob Spallek; Anna Novelli; Wiebke Schüttig (BMJ Open, 2021)
Introduction Although the impact of macrolevel characteristics of health systems on socioeconomic inequity in health has been studied extensively, the impact of access characteristics on a smaller scale of health systems has received less attention. These mesolevel characteristics can influence access to healthcare and might have the potential to moderate or aggravate socioeconomic inequity in healthcare use. This scoping review aims to map the existing evidence of the association of socioeconomic inequity in healthcare use and mesolevel access characteristics of the health system.Methods and analysis In conducting the scoping review, we follow the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols Extension for Scoping Reviews. The search will be carried out in four scientific databases: MEDLINE (via PubMed), Web of Science, Scopus and PsycINFO. Main eligibility criteria are inclusion in the analysis of a measure of socioeconomic position, a measure of individual healthcare use and a mesolevel determinant of access to healthcare services. The selection process consists of two consecutive screening stages (first: title/abstract; second: full text). At both stages, two reviewers independently assess the eligibility of studies. In case of disagreement, a third reviewer will be involved. Cohen’s kappa will be calculated to report inter-rater agreement between reviewers. Results are synthesised narratively, as a high heterogeneity of studies is expected.Ethics and dissemination No primary data are collected for the presented scoping review. Therefore, ethical approval is not necessary. The scoping review will be published in an international peer-reviewed journal, and findings will be presented on national and international conferences.